Homoacetogenic Conversion of Mannitol by the Thermophilic Acetogenic Bacterium Thermoanaerobacter kivui Requires External CO2 - Moon, Jimyung; Jain, Surbhi; Müller, Volker; Basen, Mirko (Frontiers in Microbiology, 2020)
Acetogenic microorganisms utilize organic substrates such as sugars in addition to hydrogen (H2) + carbon dioxide (CO2). Recently, we reported that the thermophilic acetogenic microorganism Thermoanaerobacter kivui is among the few acetogens that utilize the sugar alcohol mannitol, dependent on a gene cluster encoding mannitol uptake, phosphorylation and oxidation of mannitol-1-phosphate to fructose-6-phosphate. Here, we studied mannitol metabolism with resting cells of T. kivui; and found that mannitol was “fermented” in a homoacetogenic manner, i.e., acetate was the sole product if HCO3– was present. We found an acetate:mannitol ratio higher than 3, indicating the requirement of external CO2, and the involvement of the WLP as terminal electron accepting pathway. In the absence of CO2 (or bicarbonate, HCO3–), however, the cells still converted mannitol to acetate, but slowly and with stoichiometric amounts of H2 formed in addition, resulting in a “mixed” fermentation. This showed that–in addition to the WLP–the cells used an additional electron sink–protons, making up for the “missing” CO2 as electron sink. Growth was 2.5-fold slower in the absence of external CO2, while the addition of formate completely restored the growth rate. A model for mannitol metabolism is presented, involving the major three hydrogenases, to explain how [H] make their way from glycolysis into the products acetate or acetate + H2.